The effects of stroke on weight transfer before voluntary lateral and forward steps - Lanza, Marcel Bahia; Gray, Vicki L. (Frontiers in Neurology, 2022)
There is a higher rate of falls in the first year after a stroke, and the ability to step in different directions is essential for avoiding a fall and navigating small spaces where falls commonly occur. The lateral transfer of weight is important for stabilizing the body before initiating a step. Hence, understanding the ability to control lateral weight transfer (WT) in different step directions might help understand falls in individuals with stroke. The present study aimed to compare the WT characteristics (onset time, duration, mediolateral center of pressure (ML COP) velocity, and ML COP displacement) and hip abduction torque preceding a lateral and forward voluntary step between individuals with stroke (paretic and non-paretic leg) and controls. Twenty individuals with stroke and ten controls performed voluntary choice reaction tests in the lateral and forward directions. Ten trials (five on each side - right and left) were performed for each step direction. The overall primary findings were that 1) the WT before a lateral step was shorter and initiated earlier, with a larger ML COP displacement and greater hip abductor torque in the stepping leg than the forward step, 2) there was greater hip abductor produced in the stance leg before a forward step than a lateral step, 3) the WT before the lateral step took longer to initiate and was slower to execute in individuals with stroke regardless of the leg 4) the WT before the forward step had more differences in the paretic than the non-paretic leg. Thus, for the first time, it was shown that the WT characteristics and hip abduction torque during the WT are different according to step direction and also appear to be impaired in individuals with stroke. These results have implications for understanding the direction that individuals with stroke are more susceptible to being unable to recover balance and are at risk of falling.